ANALISIS PENGARUH KOMPENSASI KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI (Studi pada CV. Metalindo Manunggal Karsa) - Murti, Arum Eka; Nurgraheni, Rini (Diponegoro Journal of Management, 2015)
This research is motivated decline in employee performance CV. Metalindo Manunggal Karsa. This study aimed to examine the effect of labor compensation, work discipline, and physical work environment to employee performance in CV. Metalindo Manunggal Karsa. Research data retrieval is done through questionnaires to 84 respondents employees CV. Manunggal Metalindo Karsa obtained by using the technique jenuh sampling. Then analysis of quantitative and qualitative data. Qualitative analysis is the interpretation of the data obtained from the respondents and the data obtained from the field. Data - data that has met the validity, reliability, and classical assumption, processed with SPSS (Statistical Package for Social Science) for Windows 15. Where hypothesis testing using t test showed that the three independent variables are labor compensation (X1), work discipline (X2), and the physical work environment (X3) significant positive effect on employee performance dependent variable (Y)